High-performance training for sports - Joyce, David, ....-; Lewindon, Daniel, ....- (Champaign : Human Kinetics, 2014)
High-Performance Training for Sports changes the landscape of athletic conditioning and sports performance. This groundbreaking work presents the latest and most effective philosophies, protocols and programmes for developing today's athletes. High-Performance Training for Sports features contributions from global leaders in athletic performance training, coaching and rehabilitation. Experts share the cutting-edge knowledge and techniques they've used with Olympians as well as top athletes and teams from the NBA, NFL, MLB, English Premier League, Tour de France and International Rugby. Combining the latest science and research with proven training protocols, High-Performance Training for Sports will guide you in these areas: • Optimise the effectiveness of cross-training. • Translate strength into speed. • Increase aerobic capacity and generate anaerobic power. • Maintain peak conditioning throughout the season. • Minimise the interference effect. • Design energy-specific performance programmes. Whether you are working with high-performance athletes of all ages or with those recovering from injury, High-Performance Training for Sports is the definitive guide for developing all aspects of athletic performance. It is a must-own guide for any serious strength and conditioning coach, trainer, rehabilitator or athlete.
The authoritative guide for ultimate athletic conditioning
Keywords: Krachttraining